THE APPLICATION OF THE COMMUNICATIVE LANGUAGE TEACHING METHOD IN THE LIBYAN CLASS AT A UK UNIVERSITY: LESSON PLAN, RATIONALE AND EVALUATION - Algwil, Kamila (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This study provides a rationale for a lesson plan about the implementation of the communicative language teaching method (CLT) in the Libyan class at a UK University. The aim of the lesson plan is to develop learner’s reading skills and to develop oral fluency. The lesson is aimed for adult learners at pre-intermediate level who are studying English for general purposes. The topic of the lesson is about the types of food that are eaten around the world and the geographical, economical, and lifestyle reasons for this. The resource is adapted from Libyan school’s curriculum course book and I have amended it slightly to that it is suitable for adult learners. The topic is likely to be appropriate as it is general topic, and this may enable students to enjoy it. This view is affirmed by Nuttall (1996), who believes that the best teaching should not ignore the interest in reading and this is the reason for choosing the subject “Food around the World”. Consequently, students have motivation to tell others about their famous dishes and this may possibly lead them to develop their speaking skills